2008
DOI: 10.1542/peds.2007-2620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cesarean Section on Neonatal Mortality Rates Among Very Preterm Infants in the United States, 2000–2003

Abstract: Cesarean section does seem to provide survival advantages for the most immature infants delivered at 22 to 25 weeks of gestation, independent of maternal risk factors for cesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
5
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 32 publications
8
96
5
4
Order By: Relevance
“…13 The impact of surgical delivery on mortality in very low birth weight infants is confounded by multiple variables: the maternal risk factors for neonatal morbidity and mortality, the decision of the perinatal team to invest in infants' survival and the different strata of birth weight or gestational age used to analyze the outcome. 5 Lee and Gould reported that Cesarean sections had a significant protective effect, independent of maternal risk factors, for infants with birth weights of 500 to 1499 g, 21 but these results have not been confirmed by other studies. 18,22 A study using US vital statistics data for the years 2000 to 2003 showed that Cesarean section seems to provide survival advantages for infants born from 22 to 25 weeks of gestation, independent of maternal risk factors.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…13 The impact of surgical delivery on mortality in very low birth weight infants is confounded by multiple variables: the maternal risk factors for neonatal morbidity and mortality, the decision of the perinatal team to invest in infants' survival and the different strata of birth weight or gestational age used to analyze the outcome. 5 Lee and Gould reported that Cesarean sections had a significant protective effect, independent of maternal risk factors, for infants with birth weights of 500 to 1499 g, 21 but these results have not been confirmed by other studies. 18,22 A study using US vital statistics data for the years 2000 to 2003 showed that Cesarean section seems to provide survival advantages for infants born from 22 to 25 weeks of gestation, independent of maternal risk factors.…”
Section: Discussionmentioning
confidence: 79%
“…18,22 A study using US vital statistics data for the years 2000 to 2003 showed that Cesarean section seems to provide survival advantages for infants born from 22 to 25 weeks of gestation, independent of maternal risk factors. 5 According to the World Association of Perinatal Medicine, in 2010, Cesarean delivery for fetal indication should be offered 23 for births at 24 weeks and after if there are no severe fetal anomalies or growth restrictions. Proactive management of extreme prematurity R Guinsburg et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal activity scores were calculated for each health care region on the basis of the frequency of obstetric and neonatal interventions. Some interventions included in the scores (antenatal steroids, 3 surfactant replacement, 4 or delivery at a level III center 5 ) are known to improve outcome, whereas other interventions (eg, cesarean delivery 39 and tocolysis 40 ) may have more questionable effects. The score aimed to reflect overall willingness to intervene actively on behalf of the compromised fetus or infant, not to evaluate the effect of individual interventions.…”
Section: Discussionmentioning
confidence: 99%
“…6 It should also be noted that a decision regarding the mode of delivery is separate from the decision to provide lifesustaining interventions to the infant.…”
Section: Advocating For Equality For Preterm Infantsmentioning
confidence: 99%